Closure of diastema with the aid of a palatal silicone guide: case report (Research, Society and Development, 2020)
The objective of this article is to report a clinical case in which the diastema was closed in the anterosuperior region, through direct restoration in composite resin, emphasizing the conservative and current technique, in order to restore the patient's smile and self-esteem. Patient D. B. N., 24 years old, feoderma, female, attended the School Clinic reporting dissatisfaction regarding the color and space between his anterior teeth. Clinically, a diastema of approximately 1.5 mm was observed between elements 11 and 21. It was decided to use the technique of direct restoration in composite resin, due to its advantages of better cost-benefit, quick realization, minimal or null wear of the dental structure and reversible results when compared to the use of ceramics. Previously, dental whitening was performed in-office for the best smile esthetics. Diagnostic wax-up was used to predictability the results and for confection of a palatine silicone guide, which allowed the transfer of dental morphology and greater precision of the technique. Thus, following the restorative protocol judiciously, obtained the success of the technique used and the final result encompassing clinical aesthetic concepts and patient expectations.